Vicious - Schwab, Victoria (Villians, 2018)
Victor and Eli started out as college roommates-- brilliant, arrogant, lonely boys who recognized the same sharpness and ambition in each other. In their senior year, a shared research interest in adrenaline, near-death experiences, and seemingly supernatural events reveals an intriguing possibility: that under the right conditions, someone could develop extraordinary abilities. But when their thesis moves from the academic to the experimental, things go horribly wrong.